2019
DOI: 10.1371/journal.pone.0217289
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of lung function in successfully treated tuberculosis reveals high burden of ventilatory defects and COPD

Abstract: Background Burden, phenotype and risk-factors of lung function defects in successfully treated tuberculosis cases are unclear. Methods We performed spirometry with bronchodilators in new drug-sensitive adult (≥18 years) pulmonary tuberculosis cases during the 12 months following successful treatment in India. Airflow obstruction was defined as pre-bronchodilator FEV1/FVC<5 th percentile of Global Lung Initiative mixed-ethnicity reference (lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 57 publications
2
31
0
1
Order By: Relevance
“…Our finding that restriction was the most commonly identified spirometric abnormality is similar to what has been reported from a cohort in India, where 52% of individuals had restriction and 24% had obstruction [ 10 ]. In contrast to India where obstruction was more symptomatic than restriction, we found that individuals with restriction were more symptomatic than those with obstruction alone.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our finding that restriction was the most commonly identified spirometric abnormality is similar to what has been reported from a cohort in India, where 52% of individuals had restriction and 24% had obstruction [ 10 ]. In contrast to India where obstruction was more symptomatic than restriction, we found that individuals with restriction were more symptomatic than those with obstruction alone.…”
Section: Discussionsupporting
confidence: 90%
“…At baseline, pulmonary symptoms were moderately inversely correlated with both FEV 1 (ρ = -0.28, p value 0.004) and FVC (ρ = − 0.28, p value 0.003), such that participants with worse symptoms tended to have a lower FEV 1 and FVC (Additional file 1: Figure S1). Participants with either restriction or a mixed pattern had a significantly greater symptom burden than those with normal spirometry (median [IQR] COPD Assessment Test score 10 [4-15] for restriction and 8 [2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] for mixed vs. 4 [2][3][4][5][6][7][8][9] for normal), including greater cough, chest tightness, breathlessness, and lower energy levels. In contrast, participants with obstruction did not differ with respect to symptom burden when compared to those with normal spirometry ( Fig.…”
Section: Pulmonary Restriction Has Greater Symptoms and Radiologic Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Although population-based studies have found a high prevalence of COPD in individuals with prior TB ( 13 ), recent studies have shown considerable heterogeneity in the phenotype of post-TB lung disease ( 14 ). In contrast to smoking-associated COPD, a restrictive spirometry pattern, with or without airflow obstruction, that is largely unresponsive to bronchodilators is the predominant phenotype of post-TB lung disease ( 15 ). Furthermore, bronchiectasis is a common manifestation of treated TB, which is distinct from smoking-associated COPD ( 16 ).…”
mentioning
confidence: 99%
“…Our previous work in India found up to 50% of PTB cases had impaired lung function post-treatment [ 3 ]. We also found a positive correlation between the duration of symptomatic illness prior to PTB treatment and severity of lung impairment post-treatment.…”
mentioning
confidence: 99%